High-Temperature Mechanical and Wear Behavior of Hypoeutectic Al–Si–(Cu)–Mg Alloys with Hardening Mechanisms Dictated by Varying Cu:Mg Ratios - Jaehui Bang; Yeontae Kim; Eunkyung Lee (Applied Sciences)
Enhancing damage tolerance and wear resistance in Al–Si-based alloys under thermomechanical stress remains a key challenge in lightweight structural applications. This study investigates the microstructural and tribomechanical behavior of hypoeutectic Al–Si–(Cu)–Mg alloys with varying Cu:Mg ratios (3:1 vs. 1:3) under a T6 heat treatment. Alloys A and B, with identical Si contents but differing Cu and Mg levels, were subjected to multiscale microstructural characterization and mechanical and wear testing at 25 °C, 150 °C, and 250 °C. Alloy A (Cu-rich) exhibited refined α-Al(FeMn)Si phases and homogeneously dissolved Cu in the Al matrix, promoting lattice contraction and dislocation pinning. In contrast, Alloy B (Mg-rich) retained coarse Mg2Si and residual β-AlFeSi phases, which induced local stress concentrations and thermal instability. Under tribological testing, Alloy A showed slightly higher friction coefficients (0.38–0.43) but up to 26.4% lower wear rates across all temperatures. At 250 °C, Alloy B exhibited a 25.2% increase in the wear rate, accompanied by surface degradation such as delamination and spalling due to β-AlFeSi fragmentation and matrix softening. These results confirm that the Cu:Mg ratio critically influences the dominant hardening mechanism—the solid solution vs. precipitation—and determines the high-temperature performance. Alloy A maintained up to 14.1% higher tensile strength and 22.3% higher hardness, exhibiting greater shear resistance and interfacial stability. This work provides a compositionally guided framework for designing thermally durable Al–Si-based alloys with improved wear resistance under elevated temperature conditions.